DFT + U study of structural, electronic, optical and magnetic properties of LiFePO4 Cathode materials for Lithium-Ion batteries - A K Wabeto; K N Nigussa; L D Deja (Materials Research Express)
In this study, we have investigated the structural, electronic, optical, and magnetic properties of LiFePO _4 (LFP), which is a prominent cathode material for lithium-ion batteries (LIBs). In order to analyse the properties of LFP, we have carried out the calculations using Density Functional Theory (DFT) combined with the Hubbard (U) correction (i.e., DFT + U), as implemented in the quantum-espresso (QE) code. We performed the structural optimization and found that LFP has a stable olivine structure with equilibrium parameters of a  = 4.64 Å,  b  = 5.98 Å, and c  = 10.34 Å. It is shown that LFP has a direct band gap value of 3.82 eV, which is very close to experiment values of 3.6-4.0 eV. The projected density of states (PDOS) of the LFP closely matches with experimental reports of the electronic structure of the material, where the Fe 3 d states form tight bands above the O 2 p band. The analysis of optical properties shows a significant absorption property in the visible spectrum, reflecting its additional potential for photoactive application. We have also examined the magnetic properties, which reveal that LFP exhibits antiferromagnetic ordering, which plays a critical role in the stability of the material during lithium cycling. The investigated properties of LFP in this work, thus, highlight its viability as an effective cathode material for the next-generation battery technologies with a multifaced applications.